Sublethal effects of pesticide exposure in the buff-tailed bumblebee (Bombus terrestris): novel behavioural assay approaches. - James, Laura (2021)
The aim of the work described in this thesis was to assess the potential sublethal effects of pesticide exposure on buff-tailed bumblebee (Bombus terrestris audax) mobility, navigation, learning and memory through the development of novel bee behavioural assays. The development of such comparative testing platforms adds core tools to our ability to assess sublethal outcomes across a broad behavioural range and provides a sound basis to compare pesticidal impacts across species. This is currently limited, due to a deficit of studies on non-Apis bees. In Chapter 2, core gaps in the existing use of aversive training in bee cognitive studies are highlighted. In Chapter 3, a novel thermal-visual arena was piloted to aversively condition bumblebees to locate a cool reward zone, suggesting ambient temperature as a fruitful avenue for bee aversive learning research. In Chapter 4, this was further confirmed through trials comparing aversive conditioning to other conditioning methodologies, demonstrating that B. terrestris foragers responded best to aversive conditioning elements. In Chapter 5, the thermal-visual arena was used to assess the impact, via oral exposure, of sublethal doses of the neonicotinoid insecticides thiacloprid (500 and 5000ppb) and thiamethoxam (10 and 100ppb) and the sulfoximine insecticide sulfoxaflor (5 and 50ppb) on B. terrestris navigation and learning, demonstrating that thiamethoxam prevents bees from improving in key training parameters. In Chapter 6, new ways of examining behavioural templates were explored utilising power law analyses, uncovering a speed-curvature power law present in the walking trajectories of bees. In Chapter 7, this speed-curvature power law was found to be disrupted under thiamethoxam (10 and 100ppb) exposure. In Chapter 8, potential genetic determinants of individual differences in B. terrestris learning ability were elucidated through RNA-seq analyses of ‘good’ and ‘bad’ learners. In Chapter 9, a novel colour learning assay was employed to examine imidacloprid (10ppb) impact on associative and reversal learning in B. terrestris foragers, revealing that foraging behaviours, but not learning, are affected by chronic oral exposure. The results presented in Chapters 5, 7 and 9 clearly demonstrate that low doses of pesticides can have important sublethal effects on buff-tailed bumblebees, and can affect previously unstudied parameters (e.g. power laws governing movement (Chapters 6 and 7) and that current standard toxicological assessments often miss such subtle (not immediately lethal) impacts.